Pengaruh Kreativitas dan Kepuasan Kerja terhadap Kinerja karyawan di Sekretariat Dewan Perwakilan Rakyat Daerah Sumatera Utara - Ayu Intan Pratiwi; Muhammad Irwan Padli Nasution (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Creativity is a manifestation of mental ability and curiosity to create something new. Locke (1969) defines job satisfaction as a pleasant emotional state or positive emotion that is obtained based on an evaluation of one's job or work experience. This research uses descriptive research with a qualitative approach. DPRD North Sumatra employees have creativity and satisfaction with performance that affects in developing and advancing the reputation of the DPRD North Sumatra institution where employees have ideas or ideas to achieve goals within the organization. The research conducted interviews with North Sumatra DPRD employees. They found that they were creative and based on the results of their ideas, then they were very satisfied with the results of their performance. The effectiveness of employees with poor performance on their performance and the impact of job satisfaction is a burden on the organization in developing and maintaining performance. company life and vice vers